The Traditional Knowledge Bill, 2016: Biopiracy and Protection of Cultural Rights - Khan, Afrin; Chhangani, Deepika (Christ University Law Journal, 2023)
Traditional knowledge is such knowledge which has been present and preserved by a traditional or indigenous community from time immemorial which has a market potential to be exploited commercially. The authors through this paper put forth the urgency of this critical legal issue which can be a huge monetization market for developing and culturally rich countries like India. The research has given a special focus on the historical background of various cases of biopiracy which can create a base in understanding this urgency both in terms of substantive and procedural law. As an apt description given under the Statement of Objects and Reasons of the Traditional Knowledge Bill, 2016[1], it is of urgent consideration to identify legal regulation over commercial misappropriation of Traditional Knowledge. Against this background, it would be pertinent to examine The United Nations’ Declaration on the Rights of Indigenous Peoples, 2007 (UNDRIP) with the central aim of understanding the scope and extent of protection of traditional knowledge owned by indigenous people.